A new genus of leaf beetle (Coleoptera: Chrysomelidae: Eumolpinae) from Three Kings Islands, New Zealand - Nadein, Konstantin S.; Leschen, Richard A. B. (Zootaxa, 2017)
A new genus of eumolpine chrysomelid is described from the Three Kings Islands, New Zealand: Tyrannomolpus rex gen. nov., sp. nov. Tyrannomolpus rex is the largest endemic chrysomelid species from New Zealand, and most closely resembles members of the endemic New Zealand genus Pilacolaspis Sharp. A key to genera of New Zealand Eumolpinae is provided.